Visuospatial Abilities Training with Digital Games in a Primary School - Laura Freina; Rosa Bottino (Serious Games Society, 2018)
The "A me gli occhi" project was organized to support the development and consolidation of visuospatial abilities in students of the last two years of the Italian primary school, with the hypothesis that such a training would have a positive impact on their performance in mathematics. Twenty game based training sessions were set up along the whole school year, involving two experimental classes, while another two classes served as control group. Students' mathematical abilities were measured at the beginning of the project and at the end using a math test that had been standardized on the Italian population. Results show a statistically significant improvement in the experimental group when compared to the control one for nearly all the indicators considered, confirming the initial hypothesis. ypothesis.